CUSTOMER RELATIONS MANAGEMENT IMPLEMENTATION ANALYSIS THROUGH CUSTOMER ENGAGEMENT PROGRAM PT. GRAB INDONESIA IN YOGYAKARTA (Descriptive Study of Grab Temu Seru, Ayoyog and Jogja Istimewa in Achieving Consumer Loyalty Grab Indonesia in Yogyakarta) - Intan Haniyah Herdiana; Dewi Novianti; Ida Wiendijarti (The Indonesian Journal of Communication Studies, 2018)
The problems that occur in PT Grab Indonesia that directly impact on its customers, making the company should seek to establish good relations with external parties. The purpose of this research is to know the implementation of customer relationship management through customer engagement program PT Grab Indonesia in Yogyakarta and know the supporting and inhibiting factors of program implementation. The results in this study indicate that the programs aimed at customer PT Grab Indonesia Yogyakarta include Grab Temu Seru program, promotion program "AYOYOG" Grab Car and "JOGJAISTIMEWA" for Grab Bike is part of the implementation of customer relationship management. Implementation can be seen from the use of technology and human resources owned by PT Grab Indonesia in Yogyakarta. Supporting factors can be seen from the use of technology in the form of mobile application Grab and social media that can facilitate the company in interacting with customer Grab. While the inhibiting factors can be seen from the distribution of information on the theme of the program is quite sudden from the headquarters of PT Grab Indonesia in Jakarta which impact on publication less than the maximum. The analysis shows that the program developed by Grab Yogyakarta runs well and is able to attract the attention of consumers, but not yet to the point of consumer loyalty.